Co-intelligence living and working with AI - Mollick, Ethan 1975- (W H Allen, 2024)
"From Wharton professor and author of the popular One Useful Thing Substack newsletter Ethan Mollick comes the definitive playbook for working, learning, and living in the new age of AI The release of generative AI-from LLMs like ChatGPT to image generators like DALL-E-marks a new era. We have invented technologies that boost our physical capabilities and others that automate complex tasks, but never, until now, have we created a technology that can boost our intelligence-with an impact on work and life that researchers project will be greater than that of steam power or the internet. Mollick urges us not to turn away from AI, and instead to invite AI tools to the table. He demonstrates how AI can amplify our own capacities, acting in roles from brainstorming partner to cowriter to tutor to coach, and assesses its surprising, positive impact on business and organizations. Marshalling original research from workers and teams who are leading the rest of us in embracing and leveraging AI, Mollick cuts through the hype to make a frank and eye-opening case for the real value of AI tools. Moreover, Mollick argues that the long-term impact of AI will be different from what we expect, advantaging English majors and art history experts more than coders, and impacting knowledge workers more than blue-collar workers. Co-Intelligence shows what it means for individuals and for society to think together with smart machines, and why it's imperative that we all master that skill. Co-Intelligence challenges us to utilize AI's power without losing our identity, learn from it without being misled, and harness its gifts to create a better human future. Thought-provoking, optimistic, and lucid, Co-Intelligence reveals the promise and power of generative AI"--
Keywords: Künstliche Intelligenz; Expert systems (Computer science) / Social aspects; Artificial intelligence / Social aspects; Artificial intelligence / Educational applications; Labor / Effect of technological innovations on; Education / Effect of technological innovations on; Systèmes experts (Informatique) / Aspect social; Intelligence artificielle / Aspect social; Intelligence artificielle / Applications en éducation; Travail / Effets des innovations sur; Éducation / Effets des innovations sur